KUALITAS TIDUR MAHASISWA PROGRAM STUDI DIPLOMA III ANALIS KIMIA JURUSAN TEKNIK KIMIA (Politeknik Kesehatan Kemenkes Bandung, 2020)
This research is motivated by Fenny & Supriatmo (2016) research on the quality and quantity of sleep of students that as many as 185 of 300 students (61.7%) experience poor sleep quality. Disruption of the quality and quantity of sleep will affect the process of memory storage physiologically and psychologically adaptation. This study aims to determine the sleep quality of students of Diploma III Study Program in Chemical Analyst, Department of Chemical Engineering, State Polytechnic, Bandung. This research is a type of descriptive research with the sampling technique that is total sampling and the sample is 91 students. The data collection method is by filling out the Pittsburgh Sleep Quality Index (PSQI) questionnaire via google form and the data collected is processed by univariate analysis. The results showed that as many as 63 out of 91 students (69.2%) experienced poor sleep quality. Based on these results it can be concluded that the majority of students experience poor sleep quality. That way, students need to pay attention to sleep conditions and time management because sleep is quite influential for physical and psychological health. Keywords: Sleep quality and students